Coordination of collective action in family livestock in Uruguay - Courdin, Virginia (Sustainability in Debate, 2021)
Uruguay’s family livestock production shows an array of varied organizational arrangements, whose diversity reflects the different needs, interests, and even feelings, and values of the producers. Accordingly, cooperation processes aiming at obtaining both individual and collective benefits show different formalization and coordination frameworks. Through a series of interviews with representatives of family rancher’s group in the region known as “Litoral Norte” (Northern Coast) of Uruguay, an attempt was made understand how collective action is coordinated in the region. Results account for diverse endogenous and / or exogenous processes, which reflect the existence of shared norms, learning processes and rules of use, as a means to solve collective action problems.